PROMOVIENDO LA INCLUSIÓN EDUCATIVA A TRAVÉS DE LA EDUCACIÓN ALIMENTARIA NUTRICIONAL - Paravano, María Antonella (Universidad Nacional del Litoral, 2020)
Nutritional Education (Educación Alimentaria Nutricional, EAN) and its influence on health provide contents and skills to work at school, with the aim of improving eating behavior and quality of life. When EAN and school lunch are combined, they can directly improve the health and nutrition of students, while helping them develop good eating habits.This can be applied in all the stages of life, and it has a special importance during childhood, adolescence and early adulthood. Promoting healthy eating behaviors and a healthy lifestyle is essential to achieve a better quality of life. This work describes the experience carried out in 2016 in a Middle School for Adults of the City of Santa Fe, with 100 students who voluntarily participated and were attending the third and fifth years. A cross-sectional, descriptive and interpretive study was carried out. Recreational and educational workshops were designed and implemented for three consecutive weeks. Subsequently, an opinion survey was applied to the workshop participants in order to assess them.The students participated actively in each of the meetings, and they showed great interest and motivation. By using recreational and innovative strategies, it was possible to promote healthy habits, improving their knowledge about healthy lifestyles.